Pelatihan Pembuatan Batik Tulis Malangan Untuk Meningkatkan Intensi Berwirausaha Pada Ibu-Ibu PKK RT 12 RW 09 Kelurahan Sawojajar - Atika Syuliswati; Riezky Amalia; Novi Nugrahani; Imam Mulyono; Lia Agustina (P3M Politeknik Negeri Malang, 2023)
This community service activity aims to participate in empowering mothers who are members of PKK activities in the neighborhood of RT 12 RW 09 Sawojajar. The objectives of this training are enhancing knowledge of Malangan batik, enhancing entrepreneurship intentions through ideas for PKK women to try business opportunities in the Malangan batik, Enhancing knowledge to increase family income, and Enhancing knowledge of family financial management. The method used is a practical and educative training method through lectures, simulations, questions or answers, and the practice of making Malangan batik, fostering entrepreneurship intentions, ways to increase family income, and managing family finances. The result of this training is to gain new insights into the process of making batik Malangan. The training participants are also interested in starting a Malangan batik business as a form of interest in entrepreneurship and an effort to increase family income, and the training participants can prepare household budgets properly and correctly, to realize household financial health.